CONSTRUCTION DESIGN OF LIFTING SPREADER FOR LIFTING HARP EVAPORATOR USING FINITE ELEMENT METHOD - Imad, Hammad M.; setiawan, priyo agus; Primaningtyas, Widya E. (Universitas Maarif Hasyim Latif, 2023)
A company engaged in EPCC is working on a project to replace the evaporator tube element in an HRSG. Lifting equipment is needed for the element lifting process which includes vertical and horizontal lifting processes, the design and calculation of components on the spreader bar must be calculated properly, the spreader bar components include the main profile, sling, shackle & padeye. This is done so that there are no fatal work accidents for either the worker, the material being lifted, the lift plane or the spreader bar. Calculation of the components of the lifting aid is carried out to determine the dimensions of the components to be used, then also calculate the von mises stress that occurs. This study aims to streamline the lifting equipment which previously amounted to 2 spreader bars to 1 spreader bar without reducing the strength of the structure. The results of the calculation of von mises stress that occurred in the vertical position amounted to 68.89 Mpa (FEM Validation = 29.16 Mpa), with an allowable stress of 83.3 Mpa, while in the horizontal position the resulting von mises stress was 30.92 Mpa (FEM = 17.12 Mpa). Sebuah perusahaan yang bergerak di bidang EPCC sedang mengerjakan proyek penggantian elemen tube evaporator pada sebuah HRSG. Alat angkat dibutuhkan untuk proses pengangkatan elemen yang meliputi proses pengangkatan secara vertikal dan horizontal, desain dan perhitungan komponen pada spreader bar harus diperhitungkan dengan baik, komponen spreader bar meliputi main profile, sling, shackle & padeye. Hal ini dilakukan agar tidak terjadi kecelakaan kerja yang fatal baik bagi pekerja, material yang diangkat, pesawat angkat maupun spreader bar. Perhitungan komponen-komponen alat bantu angkat dilakukan untuk mengetahui dimensi komponen yang akan digunakan, kemudian juga menghitung tegangan von mises yang terjadi. Penelitian ini bertujuan untuk merampingkan alat bantu angkat yang sebelumnya berjumlah 2 spreader bar menjadi 1 spreader bar tanpa mengurangi kekuatan struktur. Hasil perhitungan von mises stress yang terjadi pada posisi vertikal sebesar 68.89 Mpa (FEM Validasi = 29.16 Mpa), dengan tegangan ijin sebesar 83.3 Mpa, sedangkan pada posisi horisontal von mises stress yang terjadi sebesar 30.92 Mpa (FEM = 17.12 Mpa).